L-ormosine oxalate as well as preparation method and application thereof
By forming eutectic/salt with oxalic acid, the problem of poor water solubility of L-Red Beanine is solved, and its absorption and antioxidant properties in the gastrointestinal tract are improved, and better bioavailability and therapeutic effects are achieved.
Patent Information
- Application Number
- CN202411362830.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The poor water solubility of L-Redumine leads to its malabsorption in the gastrointestinal tract, limiting its application in the treatment of degenerative chronic diseases induced by oxidative stress.
By forming a 1:1 eutectic/salt with oxalic acid, L-Rylene oxalate was prepared by liquid-assisted grinding to improve its solubility and bioavailability.
It improves the solubility and free radical scavenging ability of L-Red Beanine, significantly enhances its antioxidant performance in vitro, and improves bioavailability.
Smart Images

Figure CN119241416A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medicines, and in particular relates to L-ornithine oxalate and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] When administered orally, the drug must first be dissolved in gastric or intestinal fluid before it can penetrate the gastrointestinal membrane and enter the blood. Therefore, the solubility and permeability of the drug are crucial for the absorption of the drug in the gastrointestinal tract. However, according to statistics, about 90% of new chemical entities and about 40% of currently marketed drugs belong to Class II drugs (BCSII) or Class IV drugs (BCS IV) in the biopharmaceutics classification system, and have problems of poor water solubility and low bioavailability. Therefore, it is urgent to develop new formulations through various solubilization methods to improve the solubility properties of poorly soluble drugs. As an important branch of the field of crystal engineering, drug multi-component crystals (cocrystals, salts and their solvates) can combine different drug molecules in the same crystal lattice without changing the main chemical structure and pharmaceutical mechanism of action, thereby changing the physicochemical properties of the raw material. This method can improve the physicochemical properties of the raw material such as melting point, hygroscopicity, solubility, dissolution and stability, obtain better drug bioavailability, and thus obtain better drug therapeutic effects and reduce side effects.
[0004] L-tryptophan (N-Methyl-L-tryptophan) is one of the compounds extracted from the seeds of Abrus affinis, a plant of the genus Abrus in the Leguminosae family. It exhibits free radical scavenging and antioxidant properties in vitro, and therefore has the potential to be used in the preparation of drugs for treating degenerative chronic diseases induced by oxidative stress, including age-related functional decline, Alzheimer's disease, diabetes, inflammatory diseases, cardiovascular diseases, cancer, etc. However, L-tryptophan has poor water solubility, which limits its application. Summary of the invention
[0005] In order to overcome the above problems, the present invention provides an L-ornithine oxalate and a preparation method and application thereof.
[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0007] In a first aspect of the present invention, there is provided an L-ornithine oxalate, wherein the X-ray powder diffraction pattern represented by the diffraction angle 2θ has characteristic peaks at 9.76±0.2°, 11.30±0.2°, 15.04±0.2°, 15.88±0.2°, 16.40±0.2°, 17.40±0.2°, 19.42±0.2°, 22.46±0.2°, and 22.78±0.2°, and the structural formula of the L-ornithine oxalate is shown in formula (I):
[0008]
[0009] In one or more embodiments, the L-orhinine oxalate has Figure 2 X-ray powder diffraction pattern shown in .
[0010] In one or more embodiments, the L-orhinine oxalate has endothermic peaks at 224°C±2°C and 292°C±2°C as measured by DSC.
[0011] The second aspect of the present invention provides a method for preparing the L-orhinine oxalate described in the first aspect, comprising:
[0012] L-orhinine, oxalic acid and a solvent for auxiliary grinding are placed in a ball mill and ground to obtain L-orhinine oxalate.
[0013] In one or more embodiments, the molar ratio of L-orphine to oxalic acid is 1:1.
[0014] In one or more embodiments, the solvent to assist in grinding includes methanol.
[0015] In one or more embodiments, the diameter of the grinding balls used for grinding is 6-8 mm, preferably 7 mm.
[0016] In one or more embodiments, the grinding frequency is 25 to 28 Hz, preferably 26 Hz; the grinding time is 20 to 30 min, preferably 25 min.
[0017] The third aspect of the present invention provides a pharmaceutical composition comprising the L-orhinine oxalate described in the first aspect.
[0018] The fourth aspect of the present invention provides a pharmaceutical preparation comprising the L-orhinine oxalate described in the first aspect and at least one pharmaceutically acceptable excipient and / or carrier.
[0019] The excipients of the present invention refer to ingredients other than the active ingredients in a pharmaceutical composition or pharmaceutical preparation, which are non-toxic to the subject. Commonly used excipients in the art include buffers, stabilizers, preservatives or excipients, and commonly used excipients include binders, fillers, wetting agents, disintegrants, etc.
[0020] As an example, the excipients that can be used in the preparation of the present invention include but are not limited to: the excipient is selected from calcium phosphate, magnesium stearate, talc, dextrin, starch, gel cellulose, methyl cellulose, carboxymethyl cellulose sodium salt and polyvinyl pyrrolidone.
[0021] The drug carrier of the present invention can be a pharmaceutically acceptable solvent, suspending agent, vesicle, nanomaterial, etc., which is used to deliver the compound described in the first aspect of the present invention to an animal or human body. The carrier can be liquid or solid and is selected according to the planned administration method. Proteins and liposomes are also drug carriers.
[0022] Those skilled in the art can prepare the compounds of the present invention into pharmaceutical compositions or preparations using known techniques. For example, any compound (at least one compound) disclosed in the above-mentioned first aspect of the present invention is mixed with a pharmaceutical excipient, and then, if necessary, the resulting mixture is formed into a desired shape. Except for those mentioned in the present invention, pharmaceutical preparations can also be prepared according to known pharmaceutical preparations. And, except for those mentioned in the present invention, suitable pharmaceutical excipients are known in the art, for example, referring to the 2005 edition of the Handbook of Pharmaceutical Excipients (Original Fourth Edition).
[0023] The beneficial effects of the present invention are:
[0024] In the present invention, the cocrystal / salt of L-orphine and various organic acids was screened by liquid-assisted grinding method, and L-orphine oxalate was successfully prepared, and the molar ratio of L-orphine to oxalic acid was 1:1. Single crystal structure analysis shows that the asymmetric unit of L-orphine oxalate consists of an L-orphine ion and an oxalate ion. The supramolecular non-covalent interactions in L-orphine oxalate were studied by single crystal X-ray diffraction (SXRD), powder X-ray diffraction (PXRD), thermal analysis (TG / DSC), infrared spectroscopy (IR), density functional theory (DFT), Hirshfeld surface analysis and intermolecular weak interaction force analysis, and the possibility of salt formation was analyzed from the molecular level. PXRD shows that the crystalline phase of L-orphine oxalate is different from that of a single component, which is basically consistent with the single crystal simulation spectrum and has a high purity. The equilibrium solubility results of L-orphine, oxalic acid dihydrate and L-orphine oxalate show that salt formation can improve the solubility of low-solubility API (active pharmaceutical ingredient). The results of DPPH free radical scavenging ability and iron ion reducing ability showed that L-orphine oxalate showed better free radical scavenging and low concentration iron ion reducing ability than L-orphine in vitro. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 is the X-ray powder diffraction pattern of L-ABR-OXA, L-ABR and OXA;
[0027] Figure 2 is the X-ray powder diffraction pattern of L-orhinine oxalate;
[0028] Figure 3 This is a schematic diagram of the interaction structure between L-orphine and the carboxyl group of oxalic acid;
[0029] Figure 4 for the asymmetric unit and hydrogen bonding contacts of L-ABR-OXA;
[0030] Figure 5 is the hydrogen bond network model of L-ABR-OXA;
[0031] Figure 6 is the three-dimensional layered structure of L-ABR-OXA (c-axis);
[0032] Figure 7 (a) TG and (b) DSC results of OXA, L-ABR-OXA and L-ABR;
[0033] Figure 8 are the infrared spectra of L-ABR, L-ABR-OXA and OXA;
[0034] Fig. 9 is the solubility of L-ABR, OXA and L-ABR-OXA in water and PBS (n=3);
[0035] Fig.10 Plotting the d of L-ABR-OXA for the Hirshfeld surface norm and 2D fingerprint images;
[0036] Fig.11 The contribution of close contact to the Hirshfeld surface area of L-ABR-OXA;
[0037] Fig.12 The three-dimensional isosurface (left) and the color-filled image of the two-dimensional scatter plot (right) of L-ABR-OXA;
[0038] Fig.13 is the molecular electrostatic potential surface of L-ABR-OXA;
[0039] Fig.14 The scavenging effect of L-ABR-OXA, L-ABR, and OXA on DPPH free radicals;
[0040] Fig.15 It is the ability of L-ABR-OXA, L-ABR and OXA to reduce iron ions. DETAILED DESCRIPTION
[0041] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0042] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0043] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0044] The reagents and materials used in the following examples are shown in Table 1.
[0045] Table 1 Experimental reagents and materials
[0046] name factory purity L-Orthocarpine Shanghai Aladdin Biochemical Technology Co., Ltd. ≥98 Oxalic acid dihydrate Shanghai MacLean Biochemical Co., Ltd. ≥99 Methanol Sinopharm Chemical Reagent Co., Ltd. ≥99.7 acetone Sinopharm Chemical Reagent Co., Ltd. ≥99.7 Ethanol Sinopharm Chemical Reagent Co., Ltd. ≥99.7 Phosphate buffered saline Dalian Meilun Biotechnology Co., Ltd. Analytical grade DPPH Source Leaf Bio 98 Potassium ferrocyanide Tianjin Komiou Chemical Reagent Co., Ltd. Analytical grade Trichloroacetic acid Tianjin Komiou Chemical Reagent Co., Ltd. Analytical grade Ferric chloride Tianjin Komiou Chemical Reagent Co., Ltd. Analytical grade Disodium hydrogen phosphate Shanghai MacLean Biochemical Co., Ltd. 99.9 Sodium dihydrogen phosphate Shanghai MacLean Biochemical Co., Ltd. 99
[0047] Example 1
[0048] 1.1 Ultrafine powder was obtained by liquid-assisted grinding. The specific preparation method is as follows:
[0049] L-orbitol (L-ABR for short) (54.6 mg, 0.25 mmol) and oxalic acid (OXA for short) (31.5 mg, 0.25 mmol) were mixed with 30 μL of methanol in a ball mill, and ground with two 7 mm stainless steel balls at a frequency of 26 Hz for 25 min to obtain L-orbitol oxalate (L-ABR-OXA for short) ultrafine powder with a particle size of 50 to 100 nm.
[0050] 1.2 The L-orhinine oxalate crystals were collected by solution volatilization method. The specific method is as follows:
[0051] L-ABR (54.6 mg, 0.25 mmol) and OXA (31.5 mg, 0.25 mmol) were dissolved in a mixed solvent containing 10 mL of methanol and 10 mL of acetone, stirred at 40 °C for 4 h, filtered, acetic acid (0.10 mL) was added, and the filtrate was incubated at room temperature for about 30 days to harvest high-quality crystals.
[0052] Example 2
[0053] 2.1PXRD experiments were used to confirm the formation of L-ABR-OXA. The powder diffraction pattern of L-ABR-OXA showed different XRD patterns from those of L-ABR and OXA, such as Figure 1 The X-ray powder diffraction pattern of L-orhinine oxalate alone is shown in Figure 2 As shown. After the formation of L-orphine oxalate, the characteristic diffraction peaks of L-orphine 2θ at 14.62°, 24.34°, 26.82° and oxalic acid dihydrate at 2θ of 13.42°, 15.28° disappeared, and new characteristic peaks appeared at 9.76°, 11.30°, 15.04°, 15.88°, 16.40°, 17.40°, 19.42°, 22.46°, 22.78°. It shows that different crystalline phases are produced, and the disappearance of the characteristic peaks indicates that the sample is completely consumed. In addition, the results show that the powder diffraction pattern of L-ABR-OXA is highly consistent with the SXRD simulation analysis, indicating that the purity of L-ABR-OXA is high.
[0054] 2.2 The crystal structure of L-ornithine oxalate crystals was determined by single crystal X-ray diffraction. The crystallographic data are shown in Table 2.
[0055] Table 2 Crystallographic data and structure refinement parameters of L-orhinine oxalate crystals
[0056]
[0057]
[0058] The hydrogen bond geometry statistics in 2.3L-ornithine oxalate crystals are shown in Table 3.
[0059] Table 3 Hydrogen bond geometry statistics
[0060]
[0061] 2.4 The distances between carboxylic acid CO (long bond) and CO (short bond) in L-orphine-oxalic acid crystals are shown in Table 4 and Figure 3 As shown, the carboxyl group in oxalic acid interacts with the main nitrogen atom of L-orphine, and the CO (long bond) / CO (short bond) ratio is 1.016, proton transfer occurs, and an ionic bond is formed. The CO (long bond) / CO (short bond) ratio of the oxalic acid molecule is 1.060, which means it is not protonated. Therefore, it is judged that L-orhinine oxalate is synthesized.
[0062] Table 4 CO (long) and CO (short) bond lengths and ratios in L-orphine oxalic acid crystals
[0063]
[0064] SXRD showed that L-ABR-OXA crystallized in the P 21 21 2 space group, which was an orthorhombic system. The asymmetric unit contained one molecule of L-ABR and one molecule of OXA ( Figure 4 ), the molar ratio is 1:1. Figure 5 As shown, a molecule of L-ABR is bonded to an ion by hydrogen bonds. and It is linked to the three surrounding OXA molecules, and the OXA molecules are linked to each other through hydrogen bonds. The OH proton of the OXA molecule is transferred to the L-ABR to form an ionic bond. L-ABR and OXA cross-link to each other and form an infinitely extended one-dimensional chain structure. When observed along the c-axis, there is no obvious hydrogen bonding between the 2D sheets, and they are arranged in a "toothed" shape. The three-dimensional structure is formed by stacking through van der Waals forces. Figure 6 shown.
[0065] 2.5 Figure 7 As shown, the TG and DSC spectra of L-orphine have an endothermic peak at around 320°C, and the corresponding TG spectrum begins to lose weight at around 280°C, which is a melting and decomposition process until it is completely decomposed. Oxalic acid dihydrate loses about 24.5% of its weight before 100°C and loses two crystal waters. There is an endothermic peak at 188°C, corresponding to a weight loss of 59.7%. There is no weight loss before the decomposition temperature, and it is a melting and decomposition process. After the formation of L-orphine oxalate, there is no weight loss before 100°C and no water exists. There are two broader endothermic peaks at 224°C and 292°C. The salt decomposes in a nitrogen atmosphere. The endothermic peaks are located between L-orphine and oxalic acid dihydrate, indicating that after the salt is formed, the melting point is lowered compared to L-orphine. The first weight loss of 29.48% corresponds to the weight loss of OXA molecules (theoretical weight loss 29.20%), which is higher than the decomposition temperature of pure OXA. The second weight loss of 62.68% is L-ABR, which is not completely decomposed and still has about 7.8% residue. The formation of hydrogen bonds may affect the chemical properties of the product. The formation of hydrogen bonds will increase the binding force between molecules. During the melting and decomposition process, more energy is required to destroy the forces between molecules. Therefore, during the formation of eutectics or salts, the endothermic peak and decomposition temperature are mostly between the API and the ligand.
[0066] 2.6 After L-orphine and oxalic acid form salt through ionic bond interaction, the molecular conformation and stacking mode of L-orphine change, causing the peak of the corresponding functional group in the infrared spectrum to shift. Figure 8 The FT-IR spectra of L-orphine, oxalic acid dihydrate and L-orphine oxalate are shown in Figure 2. Oxalic acid dihydrate has a peak at 3483.91 cm -1 The absorption characteristic peak of -OH in the functional group -COOH is at 1689.49 cm -1 The characteristic peak at 3052.00cm is the stretching vibration peak of C=O, with a large electric dipole moment and strong absorption. -1 There is a -OH characteristic absorption peak at 3404.64cm -1 There is a characteristic NH peak at 1589.34cm -1 The characteristic peak at 3356.00cm is the stretching vibration peak of C=O. After the salt is formed, the characteristic peak of NH appears at 3356.00cm -1 The formation of hydrogen bonds causes the characteristic peak to move to a lower wave number, at 3059.47 cm -1 The -OH characteristic absorption peak is at the center, and the stretching vibration peak becomes broader.
[0067] Example 3
[0068] For API with low solubility, its solubility can be changed by forming a cocrystal / salt. For the ligand, a carboxylic acid with high solubility is selected in the present invention to form L-ornithine oxalate, and its equilibrium solubility is determined.
[0069] Specific steps:
[0070] (1) L-ABR, L-ABR-OXA, and OXA were ground separately and passed through an 80-mesh sieve.
[0071] (2) Drawing of the standard curve of L-orchidine
[0072] Weigh 10 mg of L-orphine accurately, dissolve it in 50 mL of water, and dilute it to 100 mL with methanol. Use chromatographic methanol to dilute the L-orphine solution, and measure it by high performance liquid chromatography. The injection volume is 2, 4, 6, 8, 12, 16, 20, 24 μL, and a standard curve is drawn. The regression equation is Y = 1396.7X + 32.389, R 2 =0.998, where Y represents the peak area, X represents the amount of L-orphine, μg, and R is the relative standard deviation.
[0073] (3) Drawing of the standard curve of oxalic acid dihydrate
[0074] Weigh 2g of oxalic acid dihydrate accurately, dissolve it in 50mL of water, and dilute it to 100mL with methanol. Use chromatographic methanol to dilute the oxalic acid dihydrate solution, and measure it by high performance liquid chromatography. The injection volume is 1, 2, 4, 6, 8, 12, 16, 24μL respectively. The regression equation is Y=360.88X+195.61, R 2 =0.998, where Y represents the peak area, X represents the amount of oxalic acid dihydrate, μg, and R is the relative standard deviation.
[0075] (4) Solubility determination of L-ABR, L-ABR-OXA, and OXA
[0076] The solubility test was conducted in water: each powder sample was added in excess to 100 mL of ultrapure water, stirred at 25°C for 24 h, the slurry was filtered out and appropriately diluted for HPLC determination, and the determination was repeated three times. The solubility test was conducted in phosphate buffer (PBS, pH = 7.4): an excess of powder sample was added to 30 mL of PBS, stirred at 37°C for 24 h, the slurry was filtered through a 0.22 μm filter membrane, and appropriately diluted, and the determination was repeated three times.
[0077] The instrument model of the high performance liquid chromatograph used in the above experiment is Agilent 1260, reverse phase column (C18, 250mm×4.6mm, filler particle size: 5μm); the configuration of L-orphine mobile phase: A: 0.2% formic acid aqueous solution, B: acetonitrile. Concentration gradient: 0-20min: 95-87% A, 20-25min: 87%-85.5% A. The injection volume is 2μL. The mobile phase flow rate is 1.0mL / min, and the separation column temperature is maintained at 30℃. The UV detection wavelength is set to 278nm. The configuration of oxalic acid dihydrate mobile phase: 30% A: 1mL formic acid + 200mL methanol, deionized water is adjusted to 1000mL, 70% B: deionized water. The injection volume is 2μL. The mobile phase flow rate is 1.0mL / min, and the separation column temperature is maintained at 30℃. The UV detection wavelength is set to 212nm.
[0078] The results are as follows Fig. 9 As shown in the figure, in 25℃ water and 37℃ PBS, the solubility of L-orphine and the ligand oxalic acid dihydrate is very different. The solubility of L-orphine oxalate formed by the two is significantly increased compared with L-orphine. One reason may be that the hydrogen bonds formed between the salts are weaker, the pH of the solution changes, and it is easier to combine with water molecules to increase the solubility. The second reason may be that the addition of the ligand changes the spatial stacking mode of L-orphine, reduces the lattice energy, and increases the solubility. It can be seen that the formation of salts can increase the solubility of low-solubility APIs, which can affect bioavailability.
[0079] Example 4
[0080] Density Functional Theory Studies
[0081] Hirshfeld surface analysis was performed to characterize the contribution (%) of various intermolecular contacts in the supramolecule. Hirshfeld surface plots and 2D fingerprint plots were generated using CrystalExplorer 21.5. Extensive density functional theory (DFT) calculations were used to understand and predict intermolecular interaction forces. In this study, the B3LYP functional was used to perform all calculations. The 6-31G(d) basis set was used for all hydrogen atom geometry optimizations and single point energy calculations, respectively. The Gaussian 16 software package was used for all calculations. Electrostatic potential (ESP), intermolecular interaction forces (IRI) were calculated using Multiwfn software and visualized by VMD software.
[0082] (1) Hirshfeld surface analysis
[0083] The Hirshfeld surface visualization was used to characterize the interaction sites of L-ABR-OXA. The Hirshfeld surface of L-ABR-OXA is shown in Fig.10 As shown, the red and blue areas indicate high and low interaction strengths, respectively. High interactions are shown as red dots on the Hirshfeld surface, corresponding to H···O contacts, which represent dnorm shorter than the sum of the van der Waals radii. 2D fingerprints and percentage contributions of contact interactions. The highlighted blue and the position of the spikes are related to the area and strength of the contacts. O···H, H···H, and C···H contacts are the main ones, accounting for 44.3%, 31.3%, and 18.5% of the intermolecular interactions, respectively. The contribution of molecular interactions between each molecule of L-ABR-OXA can be quantified by analyzing the Hirshfeld surface, and the NH···O bonds play a key role in the construction of the crystal structure. Fig.11 is the percentage of each molecule in L-ABR-OXA contributing to the Hirshfeld surface area. O···H in OXA (L-ABR-OXA) occupies the largest Hirshfeld surface area of 76.8%, while H···H and O···H in L-ABR (L-ABR-OXA) occupy a large proportion of the Hirshfeld surface area, which are 39.5% and 33.6%, respectively. Strong hydrogen bond / ionic bond interaction O3-H3A···O5, N1 + -H1B···O5 - The corresponding 2D fingerprint is two peaks H···O and O···H, and the peak lengths correspond to the interaction of distance.
[0084] (2) Weak interactions between molecules
[0085] The IRI method graphically examines the chemical bonds and weak interactions of L-ABR-OXA. It is an advanced method for evaluating the type, strength and location of intermolecular interactions in the image through isosurfaces. Green represents van der Waals interactions, red represents strong repulsive interactions (steric effects in rings and cages, etc.), and blue represents strong attractive interactions (hydrogen bonds, strong halogen bonds, etc.). Fig.12 The covalent bonds, intra-ring steric regions, intermolecular hydrogen bonds and van der Waals interaction regions of L-ABR-OXA are clearly shown. The isosurface is 1, where oxygen atoms, carbon atoms, nitrogen atoms and hydrogen atoms are represented by red, cyan, silver and white, respectively. + -H1B···O5 - The position is a blue surface, which is an ionic bond, and is represented by a blue peak in the scatter plot. The large green area indicates that the main weak interaction between the two molecules is the van der Waals effect. The middle position of the benzene ring is displayed in red, indicating the presence of steric hindrance. In the scatter plot, each point corresponds to a grid point in three-dimensional space. The more scattered points represent stronger electron density and greater contribution to the total weak interaction. The peak of sign(λ2)ρ near -0.01 to 0.01 represents the van der Waals interaction force, and positive and negative represent attraction and repulsion.
[0086] (3) Electrostatic potential (ESP)
[0087] Fig.13 This is the surface diagram of the molecular electrostatic potential of L-ABR-OXA. The colors from negative to positive are blue, white, and red. The minimum value of L-ABR-OXA is on the O atom (-55.82 kcal / mol), which acts as a hydrogen bond acceptor to form hydrogen bonds O1-H1···O6. The maximum positive potential is +66.76 kcal / mol, and the hydrogen atom on the -COOH group acts as a hydrogen donor. The red area appears near the long chain of L-ormosine, representing the nucleophilic area, which obtains protons to form ionic bonds N1 + -H1B···O5 - Because the electrostatic potential represents the range potential near the atom, it is not specific to a single atom. It can only observe the bonding trend between atoms from a macroscopic perspective, and cannot determine the energy between atoms that form hydrogen bonds.
[0088] Example 5
[0089] DPPH free radical scavenging ability assay
[0090] Under light protection, take 2mL of the test solution and 3mL of DPPH-ethanol solution, shake well, incubate at 50℃ for 30min, and measure the absorbance at 517nm; take 2mL of ethanol and mix with 3mL of DPPH-ethanol solution, and measure the absorbance at 517nm; take 2mL of the test solution and mix with 3mL of ethanol, and measure the absorbance at 517nm. Select vitamin C (0.5mg / mL) as the positive control, and calculate the DPPH free radical scavenging rate formula as follows:
[0091]
[0092] Wherein: R is the free radical scavenging rate, %; A0 is the absorbance of the blank group; A1 is the absorbance of the sample group; A2 is the absorbance of the control group.
[0093] Fig.14 In order to compare the DPPH free radical scavenging ability of L-orphine, oxalic acid dihydrate and L-orphine oxalate, a control group was set up in this experiment. The DPPH free radical scavenging ability of vitamin C with a mass concentration of 0.5 mg / mL was 95.58%, and the experimental method was feasible. The experimental results showed that the DPPH free radical scavenging ability was positively correlated with the concentrations of L-orphine, oxalic acid dihydrate and L-orphine oxalate. When the concentration was 0-1000 μg / mL, the DPPH free radical scavenging ability of L-orphine-oxalate was much greater than that of L-orphine and oxalic acid dihydrate, up to 92%, and had good DPPH free radical scavenging ability. After the concentration reached 800 μg / mL, the DPPH free radical scavenging ability was basically the same, and too high a concentration may also inhibit the DPPH free radical scavenging ability.
[0094] Example 6
[0095] Ferrous ion reducing capacity determination
[0096] Take 2.5mL of the test solution, add 2.5mL of 0.2mol / L phosphate buffer (pH=6.6) and 2.5mL of 1% potassium ferricyanide solution in sequence, mix well, cool rapidly after 20min in a 50℃ water bath, add 2.5mL of 10% trichloroacetic acid solution, mix well, take 2.5mL of the supernatant, add 2.5mL of distilled water and 0.5mL of 0.1% FeCl3 solution, mix and let stand for 10min, measure the absorbance at 700nm, select vitamin C (0.5mg / mL) as the positive control, and the reducing ability is expressed by the absorbance value.
[0097] Fig.15The figure is a comparison of the iron ion reducing ability of L-orphine, oxalic acid dihydrate and L-orphine-oxalate. The experimental results show that the iron ion reducing ability of oxalic acid dihydrate is basically 0, while the iron ion reducing ability of L-orphine and L-orphine-oxalate increases with the increase of concentration. When the concentration is 0-180μg / mL, the iron reducing ability of L-orphine-oxalate is higher than that of L-orphine. With the increase of concentration, the iron reducing ability of L-orphine increases significantly. It is inferred that L-orphine in L-orphine-oxalate plays a role in iron ion reducing ability. Therefore, at the same mass concentration, the iron reducing ability of L-orphine is greater than that of L-orphine-oxalate.
[0098] In the present invention, the cocrystal / salt of L-orphine and various organic acids was screened by liquid-assisted grinding method, and L-orphine oxalate was successfully prepared, and the molar ratio of L-orphine to oxalic acid was 1:1. Single crystal structure analysis shows that the asymmetric unit of L-orphine oxalate consists of an L-orphine ion and an oxalate ion. The supramolecular non-covalent interactions in L-orphine oxalate were studied by single crystal X-ray diffraction (SXRD), powder X-ray diffraction (PXRD), thermal analysis (TG / DSC), infrared spectroscopy (IR), density functional theory (DFT), Hirshfeld surface analysis and intermolecular weak interaction force analysis, and the possibility of salt formation was analyzed from the molecular level. PXRD shows that the crystalline phase of L-orphine oxalate is different from that of a single component, which is basically consistent with the single crystal simulation spectrum and has a high purity. The equilibrium solubility results of L-orphine, oxalic acid dihydrate and L-orphine oxalate show that salt formation can improve the solubility of low-solubility API (active pharmaceutical ingredient). The results of DPPH free radical scavenging ability and iron ion reducing ability showed that L-orphine oxalate showed better free radical scavenging and low concentration iron ion reducing ability than L-orphine in vitro.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A L-orphine oxalate, characterized in that The X-ray powder diffraction pattern represented by the diffraction angle 2θ has characteristic peaks at 9.76±0.2°, 11.30±0.2°, 15.04±0.2°, 15.88±0.2°, 16.40±0.2°, 17.40±0.2°, 19.42±0.2°, 22.46±0.2°, and 22.78±0.2°. The structural formula of L-ornithine oxalate is shown in formula (I):
2. The L-orphine oxalate according to claim 1, characterized in that It has an X-ray powder diffraction pattern shown in FIG2 .
3. The L-orphine oxalate according to claim 1, characterized in that The L-orhinine oxalate has endothermic peaks at 224°C±2°C and 292°C±2°C as measured by DSC.
4. The method for preparing L-orhinine oxalate according to any one of claims 1 to 3, characterized in that: include: L-orhinine, oxalic acid and a solvent for auxiliary grinding are placed in a ball mill and ground to obtain L-orhinine oxalate.
5. The preparation method according to claim 4, characterized in that: The molar ratio of L-orphine to oxalic acid is 1:
1.
6. The preparation method according to claim 4, characterized in that: The solvent to assist in grinding includes methanol.
7. The preparation method according to claim 4, characterized in that: The diameter of the grinding balls used for grinding is 6 to 8 mm, preferably 7 mm.
8. The preparation method according to claim 4, characterized in that: The grinding frequency is 25-28 Hz, preferably 26 Hz; the grinding time is 20-30 min, preferably 25 min.
9. A pharmaceutical composition, characterized in that The invention comprises the L-orhinine oxalate according to any one of claims 1 to 3.
10. A pharmaceutical preparation, characterized in that The invention comprises the L-orhinine oxalate according to any one of claims 1 to 3 and at least one pharmaceutically acceptable auxiliary material and / or carrier.
